Capacidade de exercício e efeitos de diferentes intensidades de exercício resistido em um treinamento físico combinado em pacientes com doença pulmonar obstrutiva crônica - Santos, Júlia Gianjoppe dos (2016)
The scientific literature of patients with Chronic Obstructive Pulmonary Disease (COPD) brings several specific aspects in relation to exercise capacity and physical training. However, there are gaps that have not been elucidated, bringing scientific questions that enabled this thesis development. The questions presented were: 1) Do patients with more symptomatic COPD present different exercise capacity on a cycle ergometer according to disease severity? 2) What limiting factors of exercise capacity are related to greater functional impairment of patients with COPD and greater disease severity? 3) In patients with COPD, which intensity of resistance training in a combined physical training produces more positive effects on peripheral muscle strength, exercise capacity, symptoms perception and quality of life? Thus, two studies were performed involving the problematic presented with following aims: 1) to identify how the limiting factors (ventilatory, cardiovascular, oxygenation and peripheral muscles) are involved in exercise performance and to determine whether there is difference on exercise capacity in more symptomatic patients with different disease severity; 2) to compare the effect of two combined trainings, different regarding the intensity of the resistance training, on peripheral muscle strength, exercise capacity, symptoms and quality of life in patients with COPD and to verify which intensity of training was capable of presenting a larger proportion of responder patients. Methods: The first study was a cross-sectional study with thirty-eight symptomatic patients with COPD (COPD assessment test ≥ 10 points) that were assessed by: Spirometry, Symptom-limited Cardiopulmonary Exercise Testing (CPET), Six Minute Walk Test (6MWT), isometric muscle strength test of knee extensors (KExt) and hip abductors (HAbd) with Microfet2 dynamometer. Subjects were grouped according to airway obstruction level [Group 1: FEV1 ≥ 50% (n=17, 66±9yrs, FEV1=61.1± 9.9%pred) and Group 2: FEV1 < 50% (n=21, 67.8±8.9yrs, FEV1=36.3±8.5%pred)]. In second study, with intervention program for patients with COPD, thirty-one patients were assessed and reassessed by: CAT, Saint George’s Respiratory Questionnaire (SGRQ); isometric muscle strength of KExt and elbow flexors (EFlex); 6MWT; Symptom-limited CPET; constant load cardiopulmonary test (CL-CPET) and one repetition maximum test (1RM). Patients were randomized in two groups and underwent 36 training sessions: combined training with low-intensity resistance training, from 30%1RM to 45%1RM for upper limbs and to 51%1RM for lower limbs (LIRT: n=16, 68.1±9.3years, 10 FEV1=50.0±15.7%pred), and combined training with high intensity resistance training, from 60%1RM to 75%1RM for upper limbs and to 81%1RM for lower limbs (HIRT: n=15, 70±6.5years, FEV 1 =46.8 ± 14.5%pred). Both groups performed aerobic training with work load corresponding to 80% VO2peak in symptom-limited CPET. Results: More symptomatic patients with more severity COPD had significantly lower 6MWD, besides lower oxygen saturation and ventilatory reserve in peak CPET, being that the prevalence of this condition in peak exercise occurred in higher proportion in this group. Furthermore, there were significant differences in isometric strength between groups, being KExt strength able to predict approximately 52% of CPET maximal load. For patients that performed combined training with different intensities of resistance training, there were significant differences regarding symptoms (CAT), quality of life (SGRQ) and exercise capacity (6MWD and Tlim) in both groups, nevertheless, only HIRT presented significative improvement in isometric muscle strength of KExt and EFlex). Both trainings presented values above the minimum clinically important difference (MCID) to symptom and exercise capacity. However, quality of life and KExt and EFlex isometric muscle strength only presented improvements higher than MCID in group HIRT, which also presented a significantly larger number of responder patients considering isometric muscle strength. Conclusion: More symptomatic patients with COPD with higher disease severity present more limitation in exercise tolerance, being lower ventilatory reserve, oxygenation deficit and KExt muscle strength more pronounced limiting factors in these patients. Additionally, aerobic training associated to resistance training was effective to improve symptoms and exercise capacity regardless the intensity of the strength training. However, high intensity resistance training may lead to greater gains regarding quality of life and peripheral muscle strength, which indicates that patients respond more and better to this intensity of training, as well as present greater clinical relevance.